Gut sensory neurons as regulators of neuro-immune-microbial interactions: from molecular mechanisms to precision therapy for IBD/IBS - Ning Sun; Li-Shuang Cao; Wan-Yu Xia; Jun-Meng Wang; Qiao-Feng Wu (Journal of Neuroinflammation)
Abstract As potentially important biosensors within the intestinal mucosal barrier, gut sensory neurons appear to dynamically orchestrate tissue homeostasis through multimodal integration of mechanical forces, chemical cues, and microbial metabolites. While current research indicates gut sensory neurons may play a significant role in the pathophysiology of IBD/IBS, the precise etiological mechanisms underlying these disorders require further investigation. In the enteric nervous system, intrinsic primary afferent neurons (IPANs) show distinct molecular characteristics compared to peripheral sensory neurons originating from the dorsal root ganglia (DRG) and vagal ganglia (NG/JG, nodose/jugular ganglia). These neuronal subtypes appear to orchestrate bidirectional epithelial-immune communication through context-dependent release of neurochemical signals, potentially establishing a dynamic neuromodulatory network. This comprehensive review will examine the latest findings on the relationship between these sensory neurons and intestinal diseases, and explore an integrated therapeutic framework based on a triple synergistic strategy. This framework could encompass precise molecular-level modulation through targeting neurotransmitters and their receptors, systemic-level neural regulation utilizing electrical nerve stimulation techniques, and ecological reprogramming mediated by gut microbiota. This potential approach may provide a possible translational pathway from mechanistic exploration to practical application, with implications for personalized clinical interventions for IBD/IBS.